KONSEP PEMBELAJARAN DIGITALISASI PERSPEKTIF AL-QUR’AN - Ahmad Sahronih (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
The concept of digitalization from the perspective of the Qur’an is capable of creating alignment and harmony between: halb ma’an-nâs (relationships among humans), halb ma’a usratih (relationships with family), and mashlahâtun li an-nâs (the welfare of humanity). The approach to applying the theory of theocentric connectivity digital learning is a theory that describes digital learning methods where learning can occur outside the individual within an organization or system and requires the ability to form connections and use networks to obtain the needed knowledge, all of which is guided by Allah’s instructions in the Qur’an, namely: practicing tabayyun in addressing news, whether it is news received or news to be conveyed to others, practicing qawlan in communication so that it aligns with prevailing ethics and norms, avoiding criticism, respecting each other, and not humiliating or harming others. In addition, adopting tazkiyyah, which purifies the mind and heart by maintaining positive thinking and a balanced attitude of mutual help in goodness, where in the learning process, all parties involved, both learners and educators, have a sense of helping each other in goodness.